Multiplex epitope detection: A new method overcomes limitations of antibody arrays. Issue 10 (3rd June 2013) - Cen, Hui; Windler, Sarah L.; Rice, Lyle S.; Zhang, Amy; Zhou, Hua
Abstract : Antibody arrays have been used as an effective method for simultaneously detecting multiple proteins such as cytokines. However, their use in quantifying a large number of cellular proteins has the following limitations: (i) unsuitable for simultaneously detecting proteins that may form complexes with each other; (ii) incapable of quantitatively detecting more than one epitope of each protein such as phospho‐ and nonphospho‐epitopes; and (iii) incapable of simultaneously detecting multiple biomarkers on solid surfaces such as formalin‐fixed tissue sections. Using a novel multiple epitope detection (MED) technique, we have overcome these limitations and have improved upon currently available antibody‐based protein detection technologies. The MED technique employs primary antibody detection of epitopes within fixed cells or tissue, followed by elution of bound antibodies, and subsequent quantification of the eluted antibodies by an epitope array. Using the MED method, we demonstrate accurate detection of individual proteins even in complex with each other, simultaneous quantitative detection of phospho‐ and nonphospho‐epitopes on a protein, and sensitive detection of multiple biomarkers on formalin‐fixed tissue sections.